Pengembangan Pembelajaran Alquran Hadis dengan Pendekatan Akal Bertingkat Ibnu Sina Di SMK Muhammadiyah 3 Yogyakarta Berbasis Neurosains Di Masa Pandemi Covid-19 - Mohammad Jailani; Suyadi Suyadi; Muallimah Muallimah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
AbstractThe COVID-19 pandemic has caused the offline learning model to turn into online learning. Including learning Al-Qur'an Hadith at SMK Muhammadiyah 3 Yogyakarta is carried out online. This causes the teaching and learning process to be less focused on student learning. Learning Al-Qur'an Hadith is not yet relevant to Ibn Sina's concept of multilevel reasoning, and brain function (Neuroscience) on student learning. This study aims to find a learning model of Al-Quran Hadith during the COVID-19 period in the perspective of Ibn Sina's multilevel reasoning based on Neuroscience studies. This research is a field research with a descriptive qualitative approach. The technique of collecting data in this research is through the results of observations, interviews, and Documentation with the Principal, Deputy Head of Curriculum, Class Guardians, Educators, and Students of SMK Muhammadiyah 3 Yogyakarta. The results of the study prove that learning Al-Quran Hadith with a neuroscience-based Ibn Sina multilevel approach is able to understand the Qur'an theoretically and empirically, both theoretically (tajwid) and reading practice (tartil).Keywords: COVID-19; Ibn Sina's stratified intellect; Neuroscience; Students and teachers; Learning Al-Quran Hadith AbstrakPandemi COVID-19 merupakan penyebab model pembelajarin offline berubah menjadi pembelajaran secara online. Termasuk pembelajaran Al-Qur’an Hadits di SMK Muhammadiyah 3 Yogyakarta dilakukan secara daring. Hal demikian menyebabkan proses belajar mengajar kurang fokus terhadap belajar peserta didik. Pembelajaran Al-Qur’an Hadits belum relevan dengan konsep akal bertingkat Ibnu Sina, dan fungsi otak (Neurosains) terhadap belajar peserta didik. Penelitian ini bertujuan menemukan model pembelajaran Al-Quran Hadits dimasa COVID-19 dalam perspektif akal bertingkat Ibnu Sina berbasis kajian Neurosains. Penelitian ini merupakan Field Research (Studi Lapangan) dengan pendekatan kualitatif deskriftif. Teknik pengumpulan data penelitian ini melalui hasil observasi, wawancara, dan Dokumentasi Bersama Kepala Sekolah, Waka Kurikulum, Wali Kelas, Pendidik, serta Peserta didik SMK Muhammadiyah 3 Yogyakarta. Hasil penelitian membuktikan bahwa pembelajaran Al-Quran Hadits dengan pendekatan akal bertingkat ibnu Sina berbasis Neurosains mampu memahami Al-Qur’an secara teoritik dan emperik baik belajar secara teori (tajwid) maupun secara praktek bacaan (tartil). Kata Kunci: COVID-19; Akal bertingkat Ibnu Sina; Neurosains; Siswa dan guru; Pembelajaran Al-Quran Hadits